The clinical relevance of anti-glutamic acid decarboxylase antibodies in children with encephalitis/encephalopathy - Hou, Ju-Yin; Liu, Hsin-Uei; Kuo, Cheng-Yen; Liu, Yi-Hsuan; Lin, Jainn-Jim; Hsieh, Meng-Ying; Hung, Po-Cheng; Cheng, Yi-Ting; Su, I-Chen; Wang, Huei-Shyong; Chou, I-Jun; Lin, Kuang-Lin (Frontiers in Neuroscience, 2023)
Anti-glutamic acid decarboxylase (anti-GAD) antibodies are associated with different types of syndromes. However, few studies have investigated the correlation between anti-GAD antibody titers with clinical severity and outcomes in children with encephalitis/encephalopathy. In this single-center retrospective cohort study, we consecutively enrolled hospitalized children who had encephalitis and/or encephalopathy with positive anti-GAD antibodies in serum and/or cerebrospinal fluid (CSF) from February 2010 to October 2021. Thirty-seven patients were included and divided into high-titer and low-titer groups. The patients with high anti-GAD antibody titers were associated with initial symptoms of language difficulty and ataxia. The level of titers was not associated with severity or outcomes. Anti-GAD antibody titers decreased after immunotherapy, however, the clinical response to immunotherapy was variable. A transient elevation in anti-GAD antibody titers during immunotherapy was noted. Further studies are warranted to investigate the role of anti-GAD antibodies in the pathogenesis and immune mechanisms of encephalitis/encephalopathy.